Factors Influencing Employee Happiness at Work: A Systematic Literature Review - Salsyabila, Nabila; Abdul Mujib (IDEA: Jurnal Psikologi, 2025)
Individuals who work with feelings of happiness is who have positive feelings at all times because he knows how to manage and influence his work world. The research method is a systematic literature review (SLR) which is carried out using the Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) and PICO (Population, Intervention, Comparison & Outcome methods to find literature that matches the research title. The selected journals are international and national journals published in 2015-2024 with quantitative methods and in English Based. On the results of the journal analysis that the author conducted on 29 journals, it was found that there are many factors that can influence happiness at work. The most influential factor on happiness at work is leadership. Based on results of the study, the researcher hopes that organizations will be able to pay attention to the factors that can influence and create a positive environment to support happiness at work for employees. If employees work with a happy feeling, they will be more productive in their work so that it provides good outcomes for an organization.